A Survey of the Collaboration Rate of Authors in the E-Learning Subject Area over a 10-Year Period (2005-2014) Using Web of Science - Mohammadi, Aeen; Asadzandi, Shadi; Malgard, Shiva (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2017)
Partnership is one of the mechanisms of scientific development, and scientific collaboration or co-authorship is considered a key element in the progress of science. This study is a survey with a scientometric approach focusing on the field of e-learning products over 10 years. In an Advanced Search of the Web of Science, the following search formula was used: TS=("m-learning" OR "mlearning" OR "mobile learning" OR "online learning" OR "virtual learning" OR "distance learning" OR "electronic learning"). The study was limited to 2005-2014, and the document type was limited to paper. A total of 4292 documents were found, to which 12362 authors contributed. The articles were evaluated individually and their information was entered into Microsoft Office Excel 2007 for analysis using the collaborative coefficient formula. In the Computers and Education journal, articles with two authors are the most frequent. The United States, with the highest production of articles in the field of e-learning, tends to produce articles with two authors. In 2014, the most productive year, articles with three authors were more frequent. The highest collaborative coefficient is in 2005 and 2014. Our findings show that despite the need for research activities as a team, the authors in the field of e-learning tend to publish their papers alone or in a team of two.